Suriname : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2019)
This Selected Issues paper on Suriname analyzes exchange rate pass through in Suriname. While the previous studies exclusively focused on the bilateral exchange rate against the US dollar, this study, in addition, estimates exchange rate passthrough using the nominal effective exchange rate. This is crucial given the strong presence of euros in the economy due to its historic connections with the Netherlands and French Guyana being one of its neighbors. The study is the first to investigate how various subcomponents of consumer price index respond to exchange rate variations differently for Suriname. The results suggest a cumulative exchange rate passthrough of around 0.4 (0.6) over six months and 0.6 (0.7) over one year for the entire sample of 1980-2019 (2000-19). A more systemic analysis suggests that the exchange rate passthrough has been declining and becoming more short-lived in recent years.